Epigenetics and adaptive phenotypic variation between habitats in an asexual snail. Issue 1 (December 2017) - Thorson, Jennifer; Smithson, Mark; Beck, Daniel; Sadler-Riggleman, Ingrid; Nilsson, Eric; Dybdahl, Mark; Skinner, Michael
Abstract In neo-Darwinian theory, adaptation results from a response to selection on relatively slowly accumulating genetic variation. However, more rapid adaptive responses are possible if selectable or plastic phenotypic variation is produced by epigenetic differences in gene expression. This rapid path to adaptation may prove particularly important when genetic variation is lacking, such as in small, bottlenecked, or asexual populations. To examine the potential for an epigenetic contribution to adaptive variation, we examined morphological divergence and epigenetic variation in genetically impoverished asexual populations of a freshwater snail, Potamopyrgus antipodarum, from distinct habitats (two lakes versus two rivers). These populations exhibit habitat specific differences in shell shape, and these differences are consistent with adaptation to water current speed. Between these same habitats, we also found significant genome wide DNA methylation differences. The differences between habitats were an order of magnitude greater than the differences between replicate sites of the same habitat. These observations suggest one possible mechanism for the expression of adaptive shell shape differences between habitats involves environmentally induced epigenetic differences. This provides a potential explanation for the capacity of this asexual snail to spread by adaptive evolution or plasticity to different environments.